Stimulation of amyloid precursor protein synthesis by adrenergic receptors coupled to cAMP formation - Lee, Robert K. K. (The National Academy of Sciences of the USA, 1997)
Amyloid plaques in Alzheimer disease are primarily aggregates of Aβ peptides that are derived from the amyloid precursor protein (APP). Neurotransmitter agonists that activate phosphatidylinositol hydrolysis and protein kinase C stimulate APP processing and generate soluble, non-amyloidogenic APP (APPs). Elevations in cAMP oppose this stimulatory effect and lead to the accumulation of cell-associated APP holoprotein containing amyloidogenic Aβ peptides. We now report that cAMP signaling can also increase cellular levels of APP holoprotein by stimulating APP gene expression in astrocytes. Treatment of astrocytes with norepinephrine or isoproterenol for 24 h increased both APP mRNA and holoprotein levels, and these increases were blocked by the β-adrenergic antagonist propranolol. Treatment with 8-bromo-adenosine 3′,5′-cyclic monophosphate or forskolin for 24 h similarly increased APP holoprotein levels; astrocytes were also transformed into process-bearing cells expressing increased amounts of glial fibrillary acidic protein, suggesting that these cells resemble reactive astrocytes. The increases in APP mRNA and holoprotein in astrocytes caused by cAMP stimulation were inhibited by the immunosuppressant cyclosporin A. Our study suggests that APP overexpression by reactive astrocytes during neuronal injury may contribute to Alzheimer disease neuropathology, and that immunosuppressants can inhibit cAMP activation of APP gene transcription.